Developmental effects of 3,4-methylenedioxymethamphetamine: a review - Skelton, Matthew R. (2008)
± 3,4-Methylenedioxymethamphetamine (MDMA) is a chemical derivative of amphetamine that has become a popular drug of abuse and has been shown to deplete serotonin in the brains of users and animals exposed to it. To date, most studies have investigated the effects of MDMA on adult animals. With a majority of users of MDMA being young adults, the chances of the users becoming pregnant and exposing the fetuses to MDMA are also a concern. Evidence to date has shown that developmental exposure to MDMA results in learning and memory impairments in the Morris water maze, a task known to be sensitive to hippocampal disruption, when the animals are tested as adults. Developmental MDMA exposure leads to hypoactivity in the offspring as adults but does not affect outcome on tests of anxiety. MDMA administration decreases pup weight, increases corticosterone and brain-derived neurotrophic factor levels during treatment while decreasing brain levels of serotonin; a decrease that initially dissipates and then reappears in adulthood. Neonatal MDMA exposure increases the sensitivity of the serotonin 1A receptor, a possible mechanism underlying the learning and memory deficits seen. Taken together, the evidence shows that MDMA exposure has adverse effects on the developing brain and behavior. The animal and human data on developmental MDMA exposure are reviewed and their public health implications discussed.